Treatment of Tuberculosis and the Drug Interactions Associated With HIV-TB Co-Infection Treatment - Pooranagangadevi, Navaneethapandian; Padmapriyadarsini, Chandrasekaran (Frontiers in Tropical Diseases, 2022)
Tuberculosis (TB) is a communicable disease that is a major source of illness, one of the ten causes of mortality worldwide, and the largest cause of death from a single infectious agent Mycobacterium tuberculosis. HIV infection and TB are a fatal combination, with each speeding up the progression of the other. Barriers to integrated treatment as well as safety concerns on the co-management of HIV- TB co-infection do exist. Many HIV TB co-infected people require concomitant anti-retroviral therapy (ART) and anti-TB medication, which increases survival but also introduces certain management issues, such as drug interactions, combined drug toxicities, and TB immune reconstitution inflammatory syndrome which has been reviewed here. In spite of considerable pharmacokinetic interactions between antiretrovirals and antitubercular drugs, when the pharmacological characteristics of drugs are known and appropriate combination regimens, dosing, and timing of initiation are used, adequate clinical response of both infections can be achieved with an acceptable safety profile. To avoid undesirable drug interactions and side effects in patients, anti TB treatment and ART must be closely monitored. To reduce TB-related mortality among HIV-TB co-infected patients, ART and ATT (Anti Tuberculosis Treatment) outcomes must improve. Clinical practise should prioritise strategies to promote adherence, such as reducing treatment duration, monitoring and treating adverse events, and improving treatment success rates, to reduce the mortality risk of HIV-TB co-infection.